Effect of different production techniques on the changes in acid and ester in sauce-flavor Baijiu - YANG Ming, ZHU Weimin, CHEN Xiangmei, GAN Linyao, WEI Heli, YANG Cheng, YANG Yun, ZHANG Jie (Zhongguo niangzao)
In this study, the effects of different stacking methods (traditional stacking, covered stacking) and fermentation time (30 d, 35 d, 40 d) on the physicochemical indexes of fermented grains and the acid and ester content in base liquor of sauce-flavor (Jiangxiangxing) Baijiu were investigated to provide a reference for optimizing the production process of sauce-flavor Baijiu. The results showed that compared with the traditional stacking, the changes of moisture and acidity in the covered stacking fermented grains were more stable, which could promote the starch consumption and increase the reducing sugar content. The contents of total acid (5.84 g/L), total ester (11.4 g/L), ethyl acetate (9.64 g/L), ethyl butyrate (2.39 g/L), acetic acid (5.5 g/L) and propionic acid (0.4 g/L) in the second round base liquor were higher than those in normal stacking fermented grains. Compared with 35 d and 40 d fermentation, the changes of moisture, acidity and reducing sugar in fermented grains at 30 d were more stable, and the reduction in total acid and total ester content of the base liquor was minimal (45%, 56%), the content of acids and esters remained at a relatively high level, which ensured the quality and stability of the liquor body. In conclusion, the covered stacking combined with fermentation 30 d significantly improved the flavor and quality stability of sauce-flavor Baijiu, providing an important reference for the improvement of its production process.